Leveraging Notice and Takedown to Address Trademark Infringement Online - Rubin, Thomas C. (The Columbia Journal of Law & the Arts, 2014)
As my background demonstrates, I understand the importance of effective enforcement for brands, and the challenges brands face in getting the job done. For that reason, I believe that we should carefully consider all reasonable proposals that would protect against consumer harm and enable trademark owners to more effectively protect their brands from commercial threats. But before turning to legislative solutions that disrupt the current legal regime, I think we must consider two big picture questions: (1) What have been the results of the current regime? Are platforms being rewarded for good behavior and held liable for bad? Are there greater opportunities for effective enforcement under current law, or is the system inherently broken? (2) What are the likely results of a change? How would a higher duty of care impact the vitality of the Internet? What is the likely impact on the integrity of the intellectual property system? What will the economic impact be? Reviewing the answers to these questions will help us to evaluate the potential pros and cons of a change to the current legal standard.